Islamic Study with An Integrative-Interdisplinary Approach - Notonegoro, Nugroho (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Islamic studies as a form of humanities discipline at the scientific level can be understood through various dimensions. Islamic studies are no longer textual or normative, but contemporary Islamic studies are more anthropocentric. The purpose of this study is to find the definition of Islamic studies both terminologically and from an integrative and interdisciplinary approach, various interdisciplinary approaches, also the urgency and purpose of Islamic studies with an interdisciplinary approach. This study uses library research methods.The findings revealed that Islamic studies with an integrative-interdisciplinary approach is a way of studying Islam and solving the challenges/problems by using a review of various relevant science to gain or achieve a greater understanding of islam and the purpose of interdisciplinary Islamic studies is to provide a more comprehensive understanding of Islam, provide an understanding of all aspects in the Al-Qur’an and Sunnah, and all aspects contained in the Al-Quran can be coherently connected.